STRATEGY OF THE MINISTRY OF RELIGION OF PEKANBARU CITY FOR THE IMPLEMENTATION OF RAUDHATUL ATHFAL (RA) LEVEL EDUCATION IN PEKANBARU CITY DURING THE 2020 COVID-19 PANDEMIC (SPECIAL STUDY OF RAUDHATUL ATHFAL (RA) IN TAMPAN DISTRICT). - Miki Bymen Putra; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The implementation of education in Indonesia in 2020 experienced enormous obstacles due to the outbreak of the Covid-19 disease, this caused a temporary cessation of the education process in Indonesia, while education is a major aspect of state life and is one of the rights of the Indonesian people. In accordance with the author's research, education at the Raudhatul Athfal (RA) level in Pekanbaru City, which is the author's research study, also experienced major obstacles in its implementation during the 2020 Covid-19 pandemic. For this reason, this study aims to analyze and find out the steps or strategies carried out by the Ministry of Religion of Pekanbaru City in the implementation of education at the Raudhatul Athfal (RA) level in Pekanbaru City, especially the Tampan District, which is a special study in the author's research. In this study the authors used Strategy Theory according to Mudrajad Kuncoro (2006), namely, two components in strategy. First; preparation of decisions made to achieve goals and second; implementation of decisions. The research method used in this research is qualitative research. This type of research is descriptive qualitative research. The research location is the Ministry of Religion of Pekanbaru City. The results of the research conducted were that there were many obstacles in the proces of Raudhatul Athfal (RA) education, especially the Tampan District, which became a red zone during the Covid-19 period in 2020. For this reason, various strategies were issued to overcome this so that education which is the right of Indonesian citizens remains goes well. For planning, the Ministry of Religion of Pekanbaru City follows the circulars and regulations handed down by the central government, after which deliberations are held by looking at the conditions of the designated zone areas. The implementation of the strategy is carried out by implementing the protocols and circulars that have been issued. This is stated in the SKB 4 of the Ministry and the study guide during the Covid-19 period. And from the analysis of its implementation, there are 4 solutions carried out in the covid-19 learning method which were permitted by the Ministry of Religion of Pekanbaru City. That is; Online, Task Pick Up System, Study Group Distribution, and Door To Dor System. Keywords: Covid-19, Strategy, Raudhatul Athfal's Education